Revisiting farm size-productivity relationship: New empirical evidence from Ethiopia. Issue 2 (3rd April 2019) - Wassie, Solomon Bizuayehu; Abate, Gashaw Tadesse; Bernard, Tanguy
ABSTRACT: Are small farms more productive? With this question in mind, this study revisits the farm size–productivity relationship and explores potential explanations using a unique plot-level data from predominantly wheat producers in Ethiopia. Overall, we find that small plots are more productive than large plots. We next test the conventional explanations hypothesised in the literature – labour market imperfection related to costly monitoring of hired workers and omitted variable bias related to soil quality – and find that neither of them essentially explains the inverse relationship. More importantly, we account for agricultural intensification and found no relationship between plot size and productivity. This suggests that the inverse relationship posited in the literature could simply arise from neglecting the impact of agricultural intensification.